Avaliação de parâmetros fisiológicos, bioquímicos e hematológicos de equinos atletas praticantes de modalidade esportiva de alta intensidade e curta duração - Cândido, Maria Lorena de Assis (2016)
Due to their privileged morphophysiological characteristics and high adaptability to extreme effort, horses have an excellent athletic profile that is highly exploited by man for high performance sports. At this level, great physical requirements caused by the adopted training can cause serious physiological, biochemical, and hematological alterations that can compromise the clinical state, well-being, and athletic performance of the animal. Literature has few sport modalities that demand fast organic responses and high-intensity, although short-lasting, physical effort, such as fast starts, agility in changing directions, abrupt stops, and great physical strength. Thus, it is necessary to expand knowledge related to animal physiology during exercise, so as to obtain greater benefit of genetic potential and individualized training. This study aimed to evaluate physiological, biochemical and hematological parameters of equine athletes training for high intensity, short duration sports in a training situation. For this, 4 Quarter Horses ± 3.5 to 7 years of age were kept in individual stalls and submitted to the same nutritional, sanitary and training management practices. A short-distance race test with intense effort was performed 3 times on a 75-meter track with an average duration of 20 seconds and at two-minute intervals. Data collection was determined at rest, immediately after the test (at the end of the third race) and 5, 20 and 50 minutes after the test. The results indicated significant increases of the physiological parameters (HR, RR and RT) biochemical parameters (lactate, CK, LDH, total protein, albumin, triglyceride cholesterol, Ca+, P+, Mg2+, Na+) and hematological parameters (hematocrit, number of red blood cells, hemoglobin and number of lymphocytes). It had been observed that At the time of the evaluated period there were significant decreases in the values of the analyzed variables, allowing to deduce that the type of physical exercise imposed proves to be effective for observation and evaluation of the behavior of the physiological, biochemical and hematological variables for high intensity, short duration stimuli and that the proposed test can be a practical tool in monitoring and vii evaluating the effects of training on the competitive modalities that require great physical effort.